Development of methods for controlling the quality of hypochlorous acid solution obtained by electrochemical synthesis - O. M. Brezvyn; I. Ya. Kotsiumbas; D. V. Hyrenko; T. V. Lukianenko; O. B. Shmychkova; L. V. Dmitrikova; O. B. Velichenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article presents materials on developing quality control methods for hypochlorite acid obtained by electrochemical synthesis. Electrochemical synthesis of hypochlorous acid was carried out using a combined electrochemical-pyrolytic method. The electrocatalytic activity of the obtained materials in the hypochlorite acid synthesis reaction was evaluated under the electrolysis of 0.05 M NaCl solutions in a duct cell with a Ti cathode at 25 ºС. The cathode area was varied, so the cathode current density was 40 mA/cm2. The pH of the solutions was monitored with a pX-150MI universal ionometer. The volumetric current density in the channel cell was 2.4 A/dm3, and the volumetric rate of solution supply was 9.5 l/h. The authors developed an original method of iodometric titration, which is based on the sequential determination of the content of hypochlorite ions, their total content with chlorite ions, and the total content simultaneously with chlorite and chlorate ions. The content of individual components of the mixture is determined as the difference between the total content of ions and the content of hypochlorite ions. The iodometric method of titration of oxidants is based on the reaction of replacing oxygen-containing compounds of chlorine with elemental iodine with its subsequent titration with standard solutions of sodium thiosulfate. It is proposed to fix the endpoint of the titration potentiometrically, which allows you to speed up the analysis, and it is also relatively easy to automate it using an automatic titrator. The content of oxygen-containing compounds in the solutions depends on the oxidation conditions and the specified operating modes of the electrochemical catalyst. The solution's acidity determines the presence of hypochlorous acid and can be calculated based on the equilibrium constant of its dissociation. The developed analysis methods will allow the control of the quality of veterinary drugs based on hypochlorous acid obtained by electrochemical synthesis.